Effect of thermal and high pressure pre-treatments and of high pressure shift freezing on green peppers firmness - Castro, S. M. (2012)
Industrially, bell peppers are usually fiozen, after being thermally blanched, to be consumed in salads after thawing. However, texture tend to decrease after this process. Therefore, several thermal (55°C) and thermalhigh-pressure (200MPa, 25°C and 55°C) pre-treatments, with and without calcium (0.50%, wlv) addition, were studied for their possible effect on texture improvement of green bell peppers. The temperature-pressure-calcium conditions revelead a significant (P<0.05) enhancement on the firmness of peppers. Peppers pre-treated at the conditions that caused the best firmness improvements were used to fürther study the effect on firmness of fieezing at atmospheric pressure and of high-pressure shift fieezing (HPSF). Only the pre-treated samples that were fiozen by HPSF (200MPa, -18°C) showed no detrimental effect on f m e s s p0.05), while those fiozen at atmospheric pressure (-l8"C, -40°C) presented a significant decrease on firmness (PK0.05). The pretreated samples showed no changes on firmness (P>0.05) after overnight storage, but after 2.5 months storage, only the high pressure pre-treated peppers showed no decrease in firmness (P>0.05), clearly indicating the beneficial effect of the high pressure pre-treatrnents to retain fmess. These results illustrate the potential of thermal, pressure, combined thermalíhigh-pressure pre-treatments on firmness improvement of green bell pepper and of HPSF to retain firmness during fieezing and frozen storage.